THE ROLE OF EXTERNALISM IN UNSAFE BUT RATIONAL REASONING - Pereira, Roberto Horácio de Sa (Kriterion, 2024)
ABSTRACT Faria’s recent publication aims to show that “if anti-individualism is correct, then the obscurity of validity is more widespread than we need to assume for present purposes.” In rejecting “a variety of exculpating moves, designed to shield the rationality of the possibly unlucky reasoner,” Faria suggests that content externalism can drastically affect our self-understanding as rational beings. I am afraid I have to disagree. Faria overintellectualizes reasoning, always performed from the first-person perspective and is subject to reflexive control by the reasoner. To be sure, content externalism shows that sound reasoning is contingent on the broad environment and therefore does not depend exclusively on the logical abilities of the living being but is a matter of logical luck. Nonetheless, content externalism is no threat to rationality. My diagnosis: By adopting Wittgenstein’s strategy of “bringing words back home,” Faria overlooks the achievements of cognitive science: in its simplest form, “transitive inference,” rationality pervades the animal kingdom. RESUMO A recente publicação de Faria tem como objetivo demonstrar que, “se o anti-individualismo estiver correto, então a obscuridade da validade é mais ampla do que necessitamos presumir para os objetivos atuais.” Através da rejeição de “uma variedade de movimentos exculpatórios, projetados para blindar a racionalidade de um pensador possivelmente azarado,” Faria sugere que o externalismo de conteúdo pode afetar drasticamente nossa autocompreensão como seres racionais. Temo que tenha que discordar. Faria superintelectualiza o pensamento, sempre performado da perspectiva de primeira pessoa e é sujeito ao controle reflexivo pelo pensador. Para ter certeza, o externalismo de conteúdo mostra que um pensamento saudável é contingente no amplo ambiente e, assim, não depende exclusivamente das habilidades lógicas do ser vivo, mas é uma questão de sorte lógica. Apesar disso, o externalismo de conteúdo não é ameaça à racionalidade. Meu diagnóstico: através da adoção da estratégia de Wittgenstein de “trazer as palavras de volta pra casa”, Faria negligencia as conquistas da ciência cognitiva: na sua forma mais simples, a “inferência transitiva,” a racionalidade pervade o reino animal.